Loco-regional administration of nanomedicines for the treatment of lung cancer. (12th October 2016) - Garrastazu Pereira, Gabriela; Lawson, Amanda Jane; Buttini, Francesca; Sonvico, Fabio
Abstract: Lung cancer poses one of the most significant challenges to modern medicine, killing thousands every year. Current therapy involves surgical resection supplemented with chemotherapy and radiotherapy due to high rates of relapse. Shortcomings of currently available chemotherapy protocols include unacceptably high levels of systemic toxicity and low accumulation of drug at the tumor site. Loco-regional delivery of nanocarriers loaded with anticancer agents has the potential to significantly increase efficacy, while minimizing systemic toxicity to anticancer agents. Local drug administration at the tumor site using nanoparticulate drug delivery systems can reduce systemic toxicities observed with intravenously administered anticancer drugs. In addition, this approach presents an opportunity for sustained delivery of anticancer drug over an extended period of time. Herein, the progress in the development of locally administered nanomedicines for the treatment of lung cancer is reviewed. Administration by inhalation, intratumoral injection and means of direct in situ application are discussed, the benefits and drawbacks of each modality are explored.